2016
DOI: 10.1097/mpg.0000000000001374
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Amino Acid−Based Formula in Infants Not Responding to Extensively Hydrolyzed Protein Formula

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
0
9
0
4
Order By: Relevance
“…AAFs are used as an option for the dietary management of CMA. It is well‐known that AAFs effectively reduce allergic symptoms and improve growth in children with CMA 11,19–22,35 . However, whether AAFs also have the potential to prevent allergic sensitization and/or symptoms associated with CMA is not known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AAFs are used as an option for the dietary management of CMA. It is well‐known that AAFs effectively reduce allergic symptoms and improve growth in children with CMA 11,19–22,35 . However, whether AAFs also have the potential to prevent allergic sensitization and/or symptoms associated with CMA is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Extensively hydrolyzed formulas (eHFs) are recommended for infants with mild CMA, whereas for infants with severe CMA and for infants who either do not tolerate eHFs or for whom eHFs fail to resolve CMA symptoms, amino acid‐based formulas (AAFs) are recommended 17 . Besides being nutritionally adequate, 18 AAFs are consistently demonstrated to provide relief and a faster recovery from symptoms of CMA, including gastrointestinal (eg, vomiting and diarrhea) and skin conditions (eg, atopic dermatitis) 11,19–21 . Moreover, nutritional intervention with an AAF has been shown to fully normalize the growth of patients with CMA 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…Compelling evidence has recently suggested that mitochondria in mammals, have multiple roles in immunity, and that in addition to being the powerhouse of the cell, they also represent the powerhouse of immunity [14]. In this light, increasing In our patient, the food allergy background led us to suspect this [17,18]. administered at an early stage of disease [19][20][21][22].…”
Section: Mitochondrial Diseases Have a Wide Spectrum Of Symptoms;mentioning
confidence: 90%
“…Paediatrician recommendations stress careful nutritional guidance to manage CMA[3,6,28,29] , including the use of an adapted formula that meets the nutritional needs of non-breastfed infants and young children[30,31]. Therefore, evidence on the safety and suitability of these formulas should be obtained from children with CMA in particular, as recently reported for some eHFs[23,24] or AAFs[32,33]. Growth parameters of the children fed the TeHCF were within normal range throughout the 3-mo period, indicating that this hypoallergenic formula is safe.…”
Section: Discussionmentioning
confidence: 99%